Deathlife Hip Hop and thanatological narrations of blackness - Pinn, Anthony B. 1964- (Duke University Press, 2024)
"Drawing on a range of theoretical frameworks including Afropessimism and Black Moralism, Deathlife uses Hip Hop to explore the ways in which Blackness serves as a framework defining and guiding the relationship between life and death in the United States. Anthony B. Pinn argues that white supremacy and white privilege operate based on the ability to distinguish death and life-to bracket off death for the sake of life. And this ability is produced and safeguarded through the construction of Blackness as death. Over against this effort to distinguish life and death, what hip hop demonstrates is the manner in which death and life are interconnected and dependent in such a way as to render them indistinguishable. Drawing on artists like Kendrick Lamar, Tyler the Creator, and Jay-Z, Deathlife argues that hip hop recognizes this dependency and explores its nature and meaning"--
Keywords: Schwarze; Tod -- Motiv; Hip-Hop; USA; Rap (Music) / Religious aspects; Rap (Music) / Social aspects; Hip-hop / Influence; African Americans / Songs and music / Social aspects; African Americans / Race identity; Death in music; Life; Noirs américains / Chants et musique / Aspect social; Noirs américains / Identité ethnique; Mort dans la musique; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies; MUSIC / Genres & Styles / Rap & Hip Hop